The infinite demand & the demand of the infinite : a theological-ethical evaluation of Simon Critchley’s experiments in political theology - Ullrich, Calvin Dieter (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2016.